Inclusive vs. Extractive Institutions in Urban Transformation: A Comparative Case Study of Hong Kong and Detroit - Ji, Zhangrong (International Journal of Social Sciences and Public Administration, 2026)
Urban centers worldwide are increasingly exposed to the twin pressures of globalization and industrial restructuring, yet their capacity to adapt varies sharply. This paper investigates the institutional determinants of divergent urban trajectories through a comparative case study of Hong Kong and Detroit. Building on Acemoglu and Robinson’s framework of inclusive versus extractive institutions, complemented by North’s theory of path dependence, we argue that institutional quality constitutes a decisive factor in shaping economic resilience at the city level. Employing a mixed-methods approach, we integrate descriptive statistics (1980–2020), policy document analysis, and process tracing of critical junctures. The findings reveal that Hong Kong’s inclusive institutions-anchored in the rule of law, market openness, and adaptive governance-enabled structural diversification from manufacturing to high value–added services, and facilitated rapid recovery from external shocks such as the 1997 Asian Financial Crisis and the 2008 Global Financial Crisis. In contrast, Detroit’s extractive institutions-dominated by rent-seeking elites, rigid union structures, and policy inertia-reinforced industrial lock-in within the automobile sector, ultimately precipitating fiscal collapse and municipal bankruptcy in 2013. This study contributes to comparative urbanism by demonstrating that national-level institutional theories are analytically powerful at the urban scale. Policy implications underscore the necessity of dismantling vested interests, embedding adaptive governance, and creating transformation funds for declining industrial cities. For emerging economies, the lessons highlight the urgency of institutional reform to prevent “Detroitization” and foster sustainable, innovation-driven growth.